2021
DOI: 10.1016/j.tice.2021.101597
|View full text |Cite
|
Sign up to set email alerts
|

Wharton jelly stem cells inhibits AGS gastric cancer cells through induction of apoptosis and modification of MAPK and NF-κB signaling pathways

Abstract: Background and aim: Gastric cancer) GC) is one of the most common cancer with high mortality worldwide. The human Wharton's jelly stem cells (hWJSCs) can inhibit several cancer cells through several molecular pathways. Therefore, the present study aimed to investigate anticancer effects of hWJSCs conditioned medium (hWJSC-CM) and cell-free lysate (hWJSC-CL) against of GC cell line AGS and underlying signaling pathways.Methods: In this study, we evaluated the effects of hWJSC-CM and hWJSC-CL on viability, proli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A higher expression of BCL2, on the other hand, inhibits apoptosis and causes cell survival (4). Therefore, the regulation of BAX and BCL2 gene expression plays a strategic role in cancer therapy (31,32). A study by Esmaeili and Farimani suggested that the S. sahandica extraction significantly contributed to the upregulation in the expression of BAX as well as to the downregulation in the expression of BCL2 in the treated breast cancer cell (33).…”
Section: Discussionmentioning
confidence: 99%
“…A higher expression of BCL2, on the other hand, inhibits apoptosis and causes cell survival (4). Therefore, the regulation of BAX and BCL2 gene expression plays a strategic role in cancer therapy (31,32). A study by Esmaeili and Farimani suggested that the S. sahandica extraction significantly contributed to the upregulation in the expression of BAX as well as to the downregulation in the expression of BCL2 in the treated breast cancer cell (33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have been performed to introduce novel natural compounds and derivatives as potential chemotherapeutic agents. In particular, pharmacological studies have significantly focused on various herbal medicine and bioactive compounds over the past two decades (24,25). This special attention to the natural compounds and herbal medicine is due to their low side effects, high efficiency, low costs, as well as targeting of cancer-related signaling pathways (26, Hydroxytyrosol is one of the most notable natural compounds which has been introduced in recent years due to its beneficial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy is one of the effective therapeutic strategies that simultaneously target multiple therapeutic anticancer pathways, such as apoptosis induction, cell cycle arrest, potential metastasis reduction, and cancer stem cell inhibition. [6,7] Doxorubicin (DOX) is one of the most common chemotherapeutic agents for several solid cancers, whether alone or in combination with other drugs or therapeutic approaches. This chemotherapy agent belongs to the anthracycline antibiotics family and is extracted from a type of mutant Streptomyces peucetius strain.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy is one of the effective therapeutic strategies that simultaneously target multiple therapeutic anticancer pathways, such as apoptosis induction, cell cycle arrest, potential metastasis reduction, and cancer stem cell inhibition. [ 6,7 ]…”
Section: Introductionmentioning
confidence: 99%